2018
DOI: 10.5216/ree.v20.46353
|View full text |Cite
|
Sign up to set email alerts
|

As relações familiares com adolescentes usuários de substâncias psicoativas: percepção dos pais

Abstract: O objetivo deste estudo consiste em discutir a experiência das famílias que cuidam de adolescentes consumidores de substâncias psicoativas, no âmbito de seu funcionamento. Estudo qualitativo, descritivo, tendo como participantes da pesquisa os genitores de adolescentes consumidores de drogas, de um Centro de Atenção Psicossocial-Álcool e Drogas do interior paulista. Foram realizadas entrevistas semiestruturadas e os dados foram analisados pela técnica de análise de conteúdo, categorial temática. Os resultados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
1
0
3
Order By: Relevance
“…One of the explanations for the association between the physical imposition of legal guardians and the use of PAS by children and adolescents under their responsibility could be that such caregivers often have difficulty in developing assertive dialogues with children and adolescents, as pointed out by Zerbetto et al (2018) in a study with parents of PAS users. Previous studies have already identified a relationship between low parental competence, school absenteeism and learning difficulties (González et al, 2016), and the relationship between the aggressive behavior of violent adolescents towards their parents and their exposure, as children, to violence within the household (Contreras & Cano, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One of the explanations for the association between the physical imposition of legal guardians and the use of PAS by children and adolescents under their responsibility could be that such caregivers often have difficulty in developing assertive dialogues with children and adolescents, as pointed out by Zerbetto et al (2018) in a study with parents of PAS users. Previous studies have already identified a relationship between low parental competence, school absenteeism and learning difficulties (González et al, 2016), and the relationship between the aggressive behavior of violent adolescents towards their parents and their exposure, as children, to violence within the household (Contreras & Cano, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, o diagnóstico de transtornos depressivos em adolescentes por vezes é complexo e trabalhoso, devido à associação dos sintomas depressivos manifestados com rebeldia e indisciplina, ocasionado pela falta de conhecimento a respeito de tal patologia (Meine & Cheiram & Jaeger, 2019). Para além disso, a depressão faz com que o adolescente se torne mais recluso e quieto, dificultando, assim, a comunicação verbal e emocional entre esta população e seus responsáveis, o que contribui para tornar essa relação mais complicada e problemática (Zerbetto, et al, 2018).…”
Section: Discussionunclassified
“…Chama a atenção a elevada prevalência de policonsumo aqui detectada, sendo que 84,9% restringir-se apenas ao adolescente que consome drogas, mas também ao sistema familiar, considerando os seus aspectos interacionais, organizacionais e comunicacionais 29 .…”
Section: Refacs (Online) Abrunclassified
“…mobilizaram na busca por recursos internos e externos à unidade familiar para desenvolver seu papel hierárquico, bem como estabelecer limites29 . Supõe-se, então, que o cuidado não pode REFACS (…”
unclassified